ANALISIS PENGARUH SUASANA TOKO DAN CITRA TOKO DALAM UPAYA MENINGKATKAN KEPUTUSAN PEMBELIAN KONSUMEN PADA LESEHAN PONDOK MIO LAHAT - armalinda, armalinda; Andayani, Melia (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2020)
In the culinary business, the lesehan business is expected to be able to implement an appropriate marketing strategy so that they can survive and win the competition in the lesehan business. Shop atmosphere and store image factors are very important in determining consumers to make a purchase. The purpose of this article is to determine whether there is an influence between store atmosphere and store image in determining Purchasing Decisions at Lesehan Pondok Mio Lahat. Secondary data shows that from 2015 to 2019, the development of lesehan businesses in Lahat Regency has increased by up to 15.5%. The results of the analysis show that the shop atmosphere and store image have a significant effect on purchasing decisions at Lesehan Pondok Mio Lahat, which means that the purchase decision will increase if the shop atmosphere is comfortable and the store image can attract consumers.